A reliable time base routing framework with seamless networking operation for SDN / Nauman Khan - Nauman , Khan (2024)
The rise of software-defined networking (SDN) has revolutionized the networking industry, offering agility and flexibility through programmable networks. As SDN adoption increases in enterprise and telecom sectors, organizations face challenges in maintaining network productivity during switch and router maintenance and upgrades and in traditional networks, also known as distributed network. This thesis presents a preventive maintenance time-based routing framework (PMTRF) to optimize the recovery of data plane failures in SDN-based networks during maintenance, such as multiple links or switch failures. The proposed framework addresses the limitations of traditional reactive and proactive approaches and focuses on enhancing backup path reliability and isolating the maintenance switch during maintenance time. By dynamically calculating the reliability of backup paths based on switch port fluctuations, the PMTRF ensures seamless and reliable network operations during maintenance. It is framed as a mixed-integer linear programming problem. To address this complexity, this work presents a multi-objective heuristic algorithm in the framework with the help of other module inputs that efficiently determines the best path for upcoming affected flows and timely isolates the maintenance switch except for the critical switch. PMTRF modules and their algorithms enable the isolation of the maintenance switch and the selection of the most reliable path for future affected flows based on input time provided by the administrator. By incorporating this approach, efficient and effective network recovery is ensured. Furthermore, identifying critical switches and their locations offers valuable information to the administrator, enabling them to avoid endto- end reachability issues during maintenance activities in the network. This work includes comprehensive experiments to assess the effectiveness of the proposed PMTRF approach. The results validate our approach’s superiority over previous methods across various performance metrics. Specifically, PMTRF approach achieves notable improvements in end-to-end delay, reducing packet loss. Additionally, it significantly reduces failure recovery time to less than 50 ms for carrier-grade networks. The proposed approach optimizes switch resource utilization by effectively managing additional flow rules in switches. Furthermore, PMTRF exhibits its resilience and adaptability to changing network conditions, accurately detects faulty switches, which is useful for fore-cast switch failures based on switch reliability within the network. By adopting PMTRF, organizations can achieve seamless and reliable network operations during maintenance, reducing downtime, increasing reliability, and improving overall network performance. This research makes a significant contribution to the field of SDN and opens avenues for future advancements in this area.